suppression of fraud and deception = قانون قمع التدليس والغش - egypt (2025)
Law no. 48 of the year 1941 on suppression of fraud and deception – ministry of trade and supply ministerial decree no. 259/1996 promulgating the executive regulations of law no. 48/1941 on suppression of fraud and deception issued on 3/7/1996 – executive regulations of Law no. 48 of the year 1941 on suppression of fraud and deception قانون رقم 48 لسنة 1941 بقمع التدليس والغش – وزارة التجارة التموين قرار وزارى رقم 259 لسنة 1996 باصدار اللائحة التنفيذية للقانون رقم 48 لسنة 1941 بقمع التدليس والغش صادر بتاريخ 3/7/1996 – اللائحة التنفيذية للقانون رقم 48 لسنة 1941 بقمع التدليس والغش المعدل بالقانون رقم 281 لسنة 1994